Engineering-ecological aspects of the management with a toxic waste at a dismantling of a floating nuclear power unit - M S Khvostova (RUDN Journal of Ecology and Life Safety, 2012)
The analytical information of the management with a toxic waste of some the enterprises of Northwest region is presented. On an example of positive experience of dismantling of nuclear submarines the look-ahead estimations of a formation of a toxic waste are executed at dismantling of the floating power unit. Sources of formation of a toxic waste, their classification and ways of the management with them are analysed.